Evaluation of a CO2-free commercial mosquito attractant to capture triatomines in the laborator - Guidobaldi, Fabio (2013)
Efforts have been made to develop vertebrate odor-based attractants to lure hematophagous triatomines into traps. However, more work is needed to reach a practical, cheap, and efficient odor lure. We carried out attraction and capture tests in a dual-choice olfactometer and a pitfall trap. Here we report that a three-component, CO2-free, synthetic blend of vertebrate odor (consisting of ammonia, L(+) lactic acid and hexanoic acid, and known as Sweetscent®) significantly induces 3rd-instar Rhodnius prolixus and Triatoma infestans nymphs to fall into the test capture-tube of the olfactometer. Blend constituents presented singly or in two-component blends did not evoke a response and, therefore, we propose that the insects respond specifically to the three-component blend in a synergistic way. When tested in a pitfall trap in an experimental arena, this blend induced capture in 37.5% of the lured traps, whereas 9% of the nymphs tested were captured in a single night. No insects were captured in control traps. Our work represents a proof-of-concept regarding capture of triatomines using host odor-based, CO2-free synthetic mixtures as lures for pitfall traps. CO2-free lures are more practical for field work than natural or CO2-containing synthetic blends.